Local Wisdom As The Foundation For Community-Based Tourism Development In Samiran, Boyolali - Cahyani Ermawati, Kris; JOI Ihalauw, John; Damiasih, Damiasih; Anggraini, Fera Dhian (Pelopor Publikasi Akademika, 2025)
This research aims to formulate a community-based tourism development model with the foundation of local wisdom in Samiran, Boyolali, Indonesia by emphasizing the strategic role of local cultural values, traditional rituals, and social practices as the main asset in creating a sustainable tourism model that preserves the environment, cultural heritage, and strengthens community welfare. This research provides practical benefits for local stakeholders, especially in empowering communities to be actively involved in tourism planning, management, and promotion. The research method used is qualitative through participatory observation, in-depth interviews, documentation, and targeted group discussions (FGD) with community leaders, tourism actors, and tourists. Data is analyzed through the stages of data reduction, triangulation, and interpretation to ensure the validity and depth of the analysis. The results of the study show that Samiran Village has a wealth of local wisdom such as the traditions of Mountain Alms, Sadranan, Temu Tirta, and Turonggo Seto which if integrated strategically can become a unique tourist attraction. However, there are still a number of challenges such as limited infrastructure, low digital literacy, and lack of professionalism in tourism management by local communities. The implications of this study confirm that local wisdom can be the foundation for the development of a competitive and sustainable rural tourism model. In practical terms, this model can be a reference for policymakers, tourism managers, and local communities in designing tourism development strategies that increase economic benefits, preserve cultural identity, and ensure environmental sustainability.